Fractal Approaches for Visualizing Huge Hierarchies - Hideki Koike; Hirotaka Yoshihara (VL'93: Proceedings of the IEEE Workshop on Visual Languages, 1993)
This paper describes fractal approaches to the problems which associate with visualizing huge hierarchies. The geometrical characteristic of a fractal, self-similarity, allows users to visually interact with a huge tree in the same manner at every level of the tree. The fractal dimension, a measure of complexity, makes it possible to control the total amount of displayed nodes. A prototype visualization system for UNIX directories is also shown.